Gifted and talented education and procedures for its promotion in the community (2013)
The idea of education of the gifted is not new in the world. It dates back to thousands of years. Despite the fact that there is a strong need to build awareness of the purposes for gifted programmes and the special needs of the students these programmes serve, developing solid advocacy effort for gifted programmes has been an overlooked area in the field. Public awareness could rescue gifted programmes from budget cuts and benign neglect by gathering much needed support, and parents can play a vital role in communicating with the public the necessity of maintaining appropriate educational experiences for gifted students. This paper specifically examined the historical perspective to Gifted and Talented Education, various definitions of giftedness, commonly used terms in Gifted Education, what makes a child Gifted or Talented, tire reasons why Gifted programmes need community support, the issue-of Equity versus Excellence and recruiting of teachers.